Experiences of Bullying for Individuals With Williams Syndrome. Issue 2 (3rd April 2017) - Fisher, Marisa H.; Lough, Emma; Griffin, Megan M.; Lane, Laurel A.
ABSTRACT: Background : Individuals with intellectual disability experience high rates of bullying, but it is not known how people with specific syndromes, such as Williams syndrome (WS), experience and respond to bullying. Given their behavioral profile, including hypersociability and heightened anxiety, and their risk for experiencing other forms of victimization, it is important to examine whether individuals with WS experience bullying and to determine how they respond. Method : Fifteen individuals with (WS) between the ages of 12 and 37 participated in semi-structured interviews about their understanding of bullying, their experiences of bullying, and how they responded. Interviews were transcribed and coded for themes related to bullying understanding, experiences, and responses. Results : Participants were able to describe bullying, often referring to bullies as mean people who want to hurt others. Individuals with WS then reported that they experienced several forms of bullying, including relational, verbal, and physical bullying. In response to bullying, the primary theme that emerged was related to self-advocacy; the participants also provided suggestions about being proud of who you are, and feeling secure within yourself about your strengths and weaknesses. Conclusions : Individuals with WS experience bullying but also stand up for themselves in the face of bullying. To inform intervention, future research should further examine the bullying experiences of individuals with WS and how they compare to individuals with other intellectual disability conditions.